„Tout à fait naturalisé“: Heines literarische Einbürgerung - Robert Krause (Recherches Germaniques)
Heine was not only recognised as a German poet but also as a French author. This is already documented by Sainte-Beuve’s reviews of the 1830s, which are examined and contextualised more closely in this article. The focus is on the linguistic and stylistic observations made by Sainte-Beuve and the enormous impact of his famous literary reviews. This paper thus sheds light on Heine’s literary naturalisation by Sainte-Beuve but also on the limitations of his method.